"Ordini mendicanti": Origini e sviluppi di una definizione identitaria - Carta, Francesco (Quaderni di storia religiosa medievale, 2025)
This paper explores the origins and developments of the expression "mendicant orders". It begins by noting that the term "mendicants" began to appear in sources from the second half of the 13th century onwards. The essay then identifies the conflict that arose in mid-century Paris between secular masters and members of the Dominican and Franciscan orders as the context in which the term emerged. It argues that, thanks to Bonaventure's reflections and Rutebeuf's literary creativity, the label "mendicants" was coined and began to spread. The analysis traces the subsequent use of the term in works leading up to the Second Council of Lyon and ultimately in the council's official canons.